2014
DOI: 10.1186/s40478-014-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Microglial pathology

Abstract: This paper summarizes pathological changes that affect microglial cells in the human brain during aging and in aging-related neurodegenerative diseases, primarily Alzheimer’s disease (AD). It also provides examples of microglial changes that have been observed in laboratory animals during aging and in some experimentally induced lesions and disease models. Dissimilarities and similarities between humans and rodents are discussed in an attempt to generate a current understanding of microglial pathology and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(207 citation statements)
references
References 145 publications
8
195
4
Order By: Relevance
“…Microglia maintain homeostasis in the healthy brain and fight infection when it is present through a complicated system of signaling molecules. The importance of microglia to neurons is supported by a higher incidence of dystrophic microglia and microglial apoptosis in AD [150]. The inflammation of the nervous system in neurodegenerative disease was thought to be due to activated microglia.…”
Section: Microglia and Neurodegenerative Diseasesmentioning
confidence: 85%
“…Microglia maintain homeostasis in the healthy brain and fight infection when it is present through a complicated system of signaling molecules. The importance of microglia to neurons is supported by a higher incidence of dystrophic microglia and microglial apoptosis in AD [150]. The inflammation of the nervous system in neurodegenerative disease was thought to be due to activated microglia.…”
Section: Microglia and Neurodegenerative Diseasesmentioning
confidence: 85%
“…In frontal and temporal grey matter, which displayed a similar burden of other pathology compared with white matter, Iba1 positive microglia were typically amoeboid, rather than dystrophic, in appearance. This dissociation between degree of microglial dystrophy and other pathology suggests that there may be region-specific microglial dystrophy in GRN mutation carriers, perhaps due to premature microglial dysfunction or senescence (Streit, Xue, Tischer, & Bechmann, 2014) secondary to GRN haploinsufficiency. As Iba1 expression may reflect microglial motility (Minett et al, 2016), microglia may be less motile in frontal white matter of GRN mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear phagocyte morphology was defined according to previous work [58] To quantify degeneration of mononuclear phagocytes in ALS patients, an observer blinded to the genotype scored from 0 to 4 the occurrence of degeneration in 2-5 sections per patient, with a score of 0 for sections showing nondegenerating phagocytes. Features of microglial degeneration were according to Streit and collaborators [58].…”
Section: Quantification Of Histological Resultsmentioning
confidence: 99%
“…However, our in vitro experiments provide an initial proof of concept that microglial survival could be influenced by serotonergic stimulation of the 5-HT 2B R. Further work is required to determine the relative contributions of microglial cell death and altered microglial phenotypes in the observed degenerative phenotype in vivo as well as the importance of monocyte degeneration. Interestingly, degeneration of mononuclear phagocytes is commonly associated with human neurodegenerative diseases, and commonly referred to as microglial degeneration [58], whereas rodent models appear less affected by this phenotype. However, previous studies observed degeneration of mononuclear phagocytes in a transgenic mutant SOD1 rat [24], similar to our current results in mutant SOD1 mice carrying a wild type Htr2b gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation